Sosialisasi Trik Menjawab Soal Reading dalam Ujian Nasional Bahasa Inggris di SMKN 1 Samatiga Aceh Barat - Endah Anisa Rahma; Rusma Setiyana (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2019)
Reading is one of the types of questions asked in National Examination. Senior High School/ MA/ SMK students face difficulties in answering reading questions because they require to analize and compare the passage. Based on the results of a study by the Research Center of the Ministry of Education and Culture (2019), only under 50% of students were able to answer the English National Examination questions. Based on these facts, it is necessary to hold a socialization about understanding English test questions and the types of questions asked in the National Examination. In this community service activity, students of SMKN 1 Samatiga who will face the National Examination are the target of the activity. This activity was carried out by lecturing, discussion and simulation test questions. After being given an understanding of the tricks in answering reading questions, the test results showed that students get scores above 50 for each aspect of the question discussed, namely: main ideas, direct and indirect questions, pronoun references, and vocabulary meaning.